IMPLEMENTASI BIMBINGAN KONSELING DALAM PEMBINAAN AKHLAK PESERTA DIDIK SMP MUHAMMADIYAH 4 PALEMBANG - Erlinda, Septi (UNISAN JURNAL, 2023)
Counseling which is one of the Guidance techniques is often said to be the core of the whole service and Guidance. Methods of data collection is done by using the method of observation, interviews and documentation. In the analysis, steps are taken to reduce data, present data and draw conclusions. As for analyzing with inductive thinking. Based on the data obtained, the results of research on the implementation of counseling guidance in moral development of students at SMP Muhammadiyah 4 Palembang showed a fairly good and significant level of change, seen from students always following counseling guidance and moral development using the method of understanding, advice, motivation, advice and habituation. So that it can slowly change the nature and habits of students for the better.